2019
DOI: 10.3390/ijerph17010137
|View full text |Cite
|
Sign up to set email alerts
|

Latent Tuberculosis Infection among Healthcare Students and Postgraduates in a Mediterranean Italian Area: What Correlation with Work Exposure?

Abstract: Background: Tuberculosis screening is part of the standard protocol for evaluating the risk of infection in healthcare workers. The aim of this study was to evaluate the prevalence of latent tuberculosis infection (LTBI) among students attending various healthcare profession degree courses and postgraduate medical courses at the School of Medicine of the University of Palermo, Italy, and assess the possible professional origin of infection. Methods: In total, 2946 students (2082 undergraduates and 864 postgrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…In fact, this low prevalence was confirmed by other studies that found prevalence rates from 2.1% to 9.9% in German trainees [ 23 , 24 ] and by two studies from Denmark [ 25 ] and Norway [ 26 ] (1% and 3.4%, respectively). Our results are also in agreement with those of several Italian studies conducted among health professionals, in which the prevalence of subjects with LTBI was very low: 0.4% in a study carried out in Northern Italy by Durando et al, 1.5% in a study by Lamberti et al, and 0.62% in a study conducted by Verso et al with both of these latter studies carried out in Southern Italy [ 27 , 28 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…In fact, this low prevalence was confirmed by other studies that found prevalence rates from 2.1% to 9.9% in German trainees [ 23 , 24 ] and by two studies from Denmark [ 25 ] and Norway [ 26 ] (1% and 3.4%, respectively). Our results are also in agreement with those of several Italian studies conducted among health professionals, in which the prevalence of subjects with LTBI was very low: 0.4% in a study carried out in Northern Italy by Durando et al, 1.5% in a study by Lamberti et al, and 0.62% in a study conducted by Verso et al with both of these latter studies carried out in Southern Italy [ 27 , 28 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Al 2015). (20,21) Overestimation of the incidence of latent tuberculosis infection with TST was probably due to BCG booster dose vaccination at birth. (16) In our study, the prevalence of LTBI in dental students was higher than in a study by Lamberti et.al in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…A study among dental students in Italy found a prevalence of 2.9% when they were tested with a tuberculin skin test (TST) and/or an interferon-y release assay (IGRA) [ 52 ]. Studies among other healthcare students showed values between 0.1% and 2.1% [ 53 , 54 , 55 , 56 ], suggesting that dental students have a higher risk of contracting tuberculosis. The fact that occupational LTBI has only been recorded since 2009 can be attributed to a change in the perception of TB as an OD, rather than to an actual increase in infections.…”
Section: Discussionmentioning
confidence: 99%